Change of liver enzymes level during follow-up of patients exposed to vinylchloride - I. V. Kudayeva; L. A. Budarina; O. A. Dyakovich (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study activity of the liver enzymes in monitoring patients exposed to vinylchloride (VC) at their professional activity.Material and methods. Prospective cohort investigation of 120 workers exposed to VC was carried out. Activity of liver enzymes was determined by kinetic methods using «Human» test-systems at «Cormay multi» biochemical analyzer.Results. It was found, that chronic VC exposition in group of service technicians and technical officers (engineering staff) at over 5 years of work experience results in decrease of alkaline phosphatases (AP) concentration, increase of contents cholinesterase (CE) and gamma-glutamyltranspeptidase (GGT) in blood serum along follow-up period. The highest count of interrelations between determinants of studied biochemical scores, work experience and-or exposition load was revealed at patients under 30 years of age.Conclusions. Chronic VC exposition results in change of AP, CE and GGT concentration in blood serum during follow-up investigation. Thus the greatest number of determining relations was revealed at patients less than 30 years. Exposition and experience played predictor role only for engineering staff, exposed to the least toxin influence.